Edoxaban Noninferior to Warfarin for Stroke Prevention in AF - Kuznar, Wayne (MD Conference Express, 2014)
This article discusses the results of the Global Study to Assess the Safety and Effectiveness of Edoxaban (DU-176b) Versus Standard Practice of Dosing With Warfarin in Patients With Atrial Fibrillation [ENGAGE-AF TIMI 48; Giugliano RP et al. N Engl J Med 2013] and new secondary analyses.